Polycyclic Aromatic Hydrocarbon-Induced Changes in Bacterial Community Structure under Anoxic Nitrate Reducing Conditions - Martirani-Von Abercron, Sophie-Marie; Pacheco, Daniel; Benito-Santano, Patricia; Marín, Patricia; Marqués, Silvia (Frontiers in Microbiology, 2016)
Although bacterial anaerobic degradation of mono-aromatic compounds has been characterized in depth, the degradation of polycyclic aromatic hydrocarbons (PAHs) such as naphthalene has only started to be understood in sulphate reducing bacteria, and little is known about the anaerobic degradation of PAHs in nitrate reducing bacteria. Starting from a series of environments which had suffered different degrees of hydrocarbon pollution, we used most probable number (MPN) enumeration to detect and quantify the presence of bacterial communities able to degrade several PAHs using nitrate as electron acceptor. We detected the presence of a substantial nitrate reducing community able to degrade naphthalene, 2-methylnaphthalene (2MN) and anthracene in some of the sites. With the aim of isolating strains able to degrade PAHs under denitrifying conditions, we set up a series of enrichment cultures with nitrate as terminal electron acceptor and PAHs as the only carbon source and followed the changes in the bacterial communities throughout the process. Results evidenced changes attributable to the imposed nitrate respiration regime, which in several samples were exacerbated in the presences of the PAHs. The presence of naphthalene or 2MN enriched the community in groups of uncultured and poorly characterized organisms, and notably in the Acidobacteria uncultured group iii1-8, which in some cases was only a minor component of the initial samples. Other phylotypes selected by PAHs in these conditions included Bacilli, which were enriched in naphthalene enrichments. Several nitrate reducing strains showing the capacity to grow on PAHs could be isolated on solid media, although the phenotype could not be reproduced in liquid cultures. Analysis of known PAH anaerobic degradation genes in the original samples and enrichment cultures did not reveal the presence of PAH-related nmsA-like sequences but confirmed the presence of bssA-like genes related to anaerobic toluene degradation. Altogether, our results suggest that PAH degradation by nitrate reducing bacteria may require the contribution of different strains, under culture conditions that still need to be defined.